Water in Alkali Aluminosilicate Glasses - Balzer, Robert; Behrens, Harald; Waurischk, Tina; Reinsch, Stefan; Müller, Ralf; Kiefer, Philipe; Deubener, Joachim; Fechtelkord, Michael (Frontiers in Materials, 2020)
To understand the influence of water and alkalis on aluminosilicate glasses, three polymerized glasses with varying ratio Na/K were synthesized [(22.5-x) Na2O - x K2O - 22.5 Al2O3 - 55 SiO2 with x = 0; 7.5; 11.25). Subsequently, these glasses were hydrated (up to 8 wt% H2O) in an internally heated gas pressure vessel. Density of hydrous glasses linearly decrease with water content above 1wt%, consistent with a partial molar volume of H2O of 12 cm3/mole. NIR spectroscopy reveal that hydroxyl groups are the dominant species at water contents < 4 wt%, and molecular water becomes dominating at water contents > 5 wt%. The fraction of OH is particularly high in the pure Na-bearing glass compared to the mixed alkali glasses. 27Al MAS-NMR spectroscopy shows that aluminum is exclusively four-fold coordinated with some variation in the local geometry. It appears that the local structure around Al becomes more ordered with increasing K/Na ratio. Incorporation of H2O reinforces this effect. Differential thermal analysis of hydrous glasses shows a significant mass loss in the range of glass transition already during the first upscan, implying high mobility of water in the glasses. This observation can be explained by the open structure of aluminosilicate network and by the low dissociation enthalpy of H2O in the glasses (≈ 8 kJ/mole). The effect of dissolved H2O on the glass transition temperature is less pronounced than for other aluminosilicate glasses, probably because of the large fraction of Al in the glasses.